Applying mobile and internet of things technologies in managing parking spaces for people with disabilities - Lambrinos, Lambros; Dosis, Aristotelis (My University, 2013)
Parking in public areas is one of the major problems faced in modern urban environments. This is more so the case for citizens with disabilities who have a limited number of spaces allocated for their exclusive use which are often not enough to meet demand and are sometimes illegitimately occupied. A smart city system that combines mobile and machine-to-machine communications has been designed aiming to alleviate the above issue. The system uses sensors to acquire disabled parking spot availability information which is disseminated to registered users in real time. Utilising such information, users can drive directly towards spots currently available or even reserve one of them. Upon arrival, legitimate users are able to verify themselves through a simple text message, a special device or a smart phone application. User verification enables more efficient monitoring of these precious parking spots.
Keywords: Mobile parking assistant; People with disabilities; Smart cities